The Tchizhevsky’s Copernican Revolution in Biology and Sociology (on the 50th death-day anniversary of the scientist) - Cabanova, N.V.; Golovanov, L.V.; Golovanov, D.L.; Myrzabayev, A.B. (Fundamental and Experimental Biology, 2015)
The message is denoted memories of the professor Alexander Leonidovich Tchizhevsky (1897–1964), founder to cosmic ecology and heliobiology, initiator of the row of the important directions in the field of sciences and technology. His name stands in one row with names Konstantin Eduardovich Tsiolkovsky and Vladimir Ivanovich Vernadsky, which symbolize shaping the cosmic direction in of natural science. They have removed the area of the theoretical thinking and practical activity of the person for limits of the usual terrestrial measurements and geocentric restrictions, and have returned due respect solar-terrestrial factor, process and phenomenas.